2018
DOI: 10.1159/000488828
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Baicalin on Diabetic Cardiac Autonomic Neuropathy Mediated by the P2Y12 Receptor in Rat Stellate Ganglia

Abstract: Background/Aims: Chronic diabetic hyperglycemia can damage various of organ systems and cause serious complications. Although diabetic cardiac autonomic neuropathy (DCAN) is the primary cause of death in diabetic patients, its pathogenesis remains to be fully elucidated. Baicalin is a flavonoid extracted from Scutellaria baicalensis root and has antibacterial, diuretic, anti-inflammatory, anti- metamorphotic, and antispasmodic effects. Our study explored the effects of baicalin on enhancing sympathoexcitatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Moreover, due to many diabetic complications share common upstream pathogenesis, published evidences have demonstrated that BAI can also improve diabetic cardiac diseases and diabetic retinopathy via inhibiting oxidative stress and MAPK-inflammation pathway. 52,53 We believe that this feature can also be deduced from other natural products with both antioxidant and anti-inflammatory properties during the treatment of diabetic complications. Additionally, these findings provided compelling evidence that Nrf2 and MAPK signaling pathways were promising targets for diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, due to many diabetic complications share common upstream pathogenesis, published evidences have demonstrated that BAI can also improve diabetic cardiac diseases and diabetic retinopathy via inhibiting oxidative stress and MAPK-inflammation pathway. 52,53 We believe that this feature can also be deduced from other natural products with both antioxidant and anti-inflammatory properties during the treatment of diabetic complications. Additionally, these findings provided compelling evidence that Nrf2 and MAPK signaling pathways were promising targets for diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, the entire dose-response curves of berberine was shown to be shifted down in the presence of baicalin (100 µmol/L), and baicalin antagonised the effect of berberine on glucose uptake in 3T3-L1 adipocytes. Since the antioxidant flavonoid baicalein is known to improve a range of abnormalities associated with diabetes [80][81][82][83][84][85], its coadministration with berberine appear to have a favourable outcome in the specified dose range.…”
Section: From Drug Combination To Structural Linkage With Other Bioacmentioning
confidence: 99%
“…The results of this study revealed that S. baicalensis augments the antidiabetic effect of metformin, probably by improving the antioxidant status (Waisundara et al, 2008). In another study, Sheng et al determined the effect of baicalin on diabetic cardiac autonomic neuropathy in high‐fat diet and streptozocin‐induced diabetic rats (Sheng et al, 2018). They suggested that baicalin (100 mg/kg, I.P.…”
Section: Resultsmentioning
confidence: 99%
“…for 14 days) diminishes the increased blood pressure, heart rate, serum epinephrine, and p38MAPK levels as well as P2Y12 receptor, interleukin (IL)‐1β, TNF‐α, and connexin 43 (Cx43) expression levels in the stellate ganglia of diabetic rats. Overall, baicalin improved diabetic cardiac autonomic neuropathy by hampering the P2Y12 receptor and sympathetic activity (Sheng et al, 2018). Ma and coworkers investigated that baicalin recuperated the diabetes‐associated cognitive deficits in rats.…”
Section: Resultsmentioning
confidence: 99%